Buying into change : mass consumption, dictatorship, and democratization in Franco's Spain, 1939-1982 - Gómez del Moral, Alejandro J. (University of Nebraska Press, 2021)
Buying into Change examines how the development of a mass consumer society under the dictatorship of Generalissimo Francisco Franco (1939-1975) inserted Spain into transnational consumer networks and set the stage for Spain's transition to democracy during the late 1970s.